Clinical randomized trial study of hearing aids effectiveness in association with Ginkgo biloba extract (EGb 761) on tinnitus improvement - Radunz,Camila L. (2020)
Abstract Introduction: Tinnitus is defined as the perception of sound without its actual presence in the environment. It has been the subject of a great number of studies, especially considering its consequences on patient's quality of life. Objective: This study aimed to investigate the effect of hearing aids and/or Ginkgo biloba extract EGb 761 on tinnitus in patients with hearing loss. Methods: This is a trial randomized-controlled treatment, parallel, double-blind, with three-arm. Thirty-three adults subjects were divided into three groups: group 1 — subjects undergoing drug therapy with Ginkgo biloba extract EGb 761; group 2 — individuals fitted with digital hearing aids; group 3 — individuals submitted to drug therapy with Ginkgo biloba extract EGb 761 and using hearing aids. The tinnitus handicap inventory and visual analogue scale were used to evaluate self-perception of tinnitus loudness and severity before treatment and 90 days after treatment. Results: This study demonstrated a significant correlation between tinnitus handicap inventory and visual analogue scale, before and after treatment. We observed a significant improvement in self-perception of tinnitus loudness and severity after 90 days of treatment with Ginkgo biloba extract EGb 761 and/or hearing aids. No correlation was found between tinnitus onset time and self-perception of tinnitus loudness and severity. Hearing aids were more effective in patients with a shorter tinnitus onset time and Ginkgo biloba extract was effective regardless of tinnitus duration. Conclusions: It was possible to prove the effectiveness of the hearing aids and/or Ginkgo biloba extract EGb 761 treatment, which shows success in the control of tinnitus contributing to the improvement of this symptom.